SGLT1: A Potential Drug Target for Cardiovascular Disease - Zhao M; Li N; Zhou H (Dove Medical Press, 2023)
Mengnan Zhao,* Na Li,* Hong Zhou Department of Endocrinology, the Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China*These authors contributed equally to this workCorrespondence: Hong Zhou, Department of Endocrinology, the Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, People's Republic of China, Tel +86 151 3011 9625, Email zhoubs2013@163.comAbstract: SGLT1 and SGLT2 are the two main members of the sodium-glucose cotransporters (SGLTs), which are mainly responsible for glucose reabsorption in the body. In recent years, many large clinical trials have shown that SGLT2 inhibitors have cardiovascular protection for diabetic and non-diabetic patients independent of lowering blood glucose. However, SGLT2 was barely detected in the hearts of humans and animals, while SGLT1 was highly expressed in myocardium. As SGLT2 inhibitors also have a moderate inhibitory effect on SGLT1, the cardiovascular protection of SGLT2 inhibitors may be due to SGLT1 inhibition. SGLT1 expression is associated with pathological processes such as cardiac oxidative stress, inflammation, fibrosis, and cell apoptosis, as well as mitochondrial dysfunction. The purpose of this review is to summarize the protective effects of SGLT1 inhibition on hearts in various cell types, including cardiomyocytes, endothelial cells, and fibroblasts in preclinical studies, and to highlight the underlying molecular mechanisms of protection against cardiovascular diseases. Selective SGLT1 inhibitors could be considered a class of drugs for cardiac-specific therapy in the future.Keywords: sodium glucose cotransporter 1, SGLT1 inhibitor, heart failure, cardioprotection, molecular mechanism